Portable savonius horizontal axis water turbine as renewable energy learning media - Hadi Nasbey; Sunaryo Sunaryo; Firmanul Catur Wibowo; Nadhira Addina Rahadian (Momentum: Physics Education Journal, 2025)
The Potential of Utilizing Water Energy as a Renewable Energy Source is Significant. Water turbines are used to convert water energy into electrical energy. Among various types of turbines, the Savonius water turbine is most suitable for low-flow water conditions in Indonesia. This research aims to develop a horizontal axis Savonius water turbine for low-flow water conditions. The turbine utilizes L-shaped blades and a deflector with a 30-degree inclination to enhance power and torque. The developed turbine has an aluminum frame with dimensions of 66 cm x 38 cm x 40 cm, while the turbine blades are made of acrylic with dimensions of 30 cm x 10 cm. Data collection was performed by varying the water velocity in 10 levels (0.4 m/s to 4 m/s) with 10 repetitions for each velocity level. The research results revealed that the maximum power output occurred at a velocity of 4 m/s, generating 0.38 Watt with a shaft rotation of 258.63 rpm. This study highlights the potential of water energy as a renewable energy Learning media and demonstrates the practical application of Savonius water turbines for environmentally friendly water energy utilization.